JC70: a new monoclonal antibody that detects vascular endothelium associated antigen on routinely processed tissue sections. Issue 9 (September 1990) - Parums, D V; Cordell, J L; Micklem, K; Heryet, A R; Gatter, K C; Mason, D Y
Abstract : A new monoclonal antibody, JC70, raised against a membrane preparation from a spleen affected by hairy cell leukaemia, recognises a membrane bound glycoprotein identical with that of the CD31 group of monoclonal antibodies. The antibody stains a fixation resistant epitope on endothelial cells in benign and malignant conditions in a wide variety of paraffin wax embedded tissue. JC70 stained malignant endothelial cells in 10 angiosarcomas with more consistency than monoclonal or polyclonal antibodies to factor VIII related antigen (FVIII-Rag). In four cases of Kaposi's sarcoma the antibody stained malignant endothelial cells but not spindle cells. It is concluded that antibody JC70 is of value for studying benign and malignant human vascular disorders in routinely processed tissue.